Foreign aid for economic growth: a case study of Uganda - Wolgast, Jackie (Graduate School of Business (GSB), 2019)
Poverty remains, despite efforts by the advanced economies to address it, a constant challenge in the world, particularly in Africa. The African continent has been riddled with poverty for decades. The factors that lead to and sustain poverty in African countries are varied and differ from country to country. However, historical factors, political instability, poor economic policies, a lack of education, disease, population growth, as well as climatic and environmental factors are key examples of some of these contributing factors. Today, Uganda is considered to be one of the poorer countries on the African continent, and for decades, despite large amounts of foreign aid inflow, there has been no significant improvement in relation to poverty reduction. The purpose of this study was to evaluate whether foreign aid contributed to economic growth in Africa, with Uganda serving as a case study. Using data from 1987 to 2011, the Autoregressive Distributed Lag was employed to test for the existence of the long-run Augmented Dickey-Fuller test for stationarity and the Ordinary Least Square regression analysis was used to test for the relationship between the variables. The results show that foreign aid has a significant negative effect on economic growth in the long run. The lesson for policymakers is that aid can improve economic growth in the long run, if and when facilitated by quality institutions. Other policy recommendations are included